Valvular pulmonary stenosis. Fonocardiográfico Study. Morphology of the curve right ventricle - Bocanegra, José (1956)
We studied 24 cases of Congenital Valvular Pulmonary Stenosis, the characters of the second pulmonary sound. - In 16 cases splitting is registered with the pulmonary component of lower intensity than the aortic, and interval between the onset of both components from 0.06 to 0.08 second, in 5 cases it was found weak but pure and in the remaining three bullrings, was pure and normal intensity. Nature of the second pulmonary noise is related to the duration of systole and right ventricular systolic pressure in the cavity. Increased right ventricular systole. conditions delay in the closure of the pulmonary leaflets. The delay in the closure of the semilunar pulmonary conditions the dissociation of the aortic and pulmonary components thus producing the splitting. The morphology of the right ventricle in 19 cases was different from other heart diseases that present with right ventricular hypertension, keeping pressure regarding ventr. right. The right ventricular systole is shortened in cases where pulmonary stenosis associated with atrial septal shunt invested and where coronary flow is compromised. This shortening of right ventricular systole, together with the known presórica and morphological differentiation can be used for differential diagnosis between Trilogy and Tetralogy of Fallot.